An integrated remediation approach using combinations of biochar, Rhizobium leguminosarum, and Vigna radiata for immobilizing and dissipating cadmium contaminants from the soil–mustard plant system - Hira, Qurat-ul-Ain Ali; Mahboob, Midhat; Azhar, Rimsha; Munir, Faiza; Gul, Alvina; Hayat, Asim; Shah, Tariq; Amir, Rabia (Frontiers in Plant Science, 2023)
Cadmium (Cd) contamination of soils is an environmental concern, as cadmium harms food crops and can therefore impact human health. The use of combinations of biochar (seeded with Rhizobium leguminosarum) and Vigna radiata (as an intercrop) has the potential to reduce the mobilization of Cd from soil via mustard plants (Brassica juncea). Mustard plants are grown as a food and oil production crop that is consumed worldwide. However, this plant has the property of hyperaccumulation; thus, it bioaccumulates Cd in its tissues, which in turn, if eaten, can become part of the human food chain. Hence, reducing Cd bioaccumulation in mustard plants is crucial to making these plants a reliable and safe source of food for consumption. To improve soil sorption capacity and immobilization efficiency, biochar (in the form of wheat husk) was mixed with R. leguminosarum and intercropped (using V. radiata) with mustard plants for further investigation. Sampling was performed at an early growth stage (i.e., at 30 days) and at maturity (i.e., at 60 days) to determine the impact of Cd on a plant’s morphophysiological attributes. Data were analyzed in two ways: first by analysis of variance (ANOVA) and then by the post hoc Tukey’s honestly significant difference (HSD) test. The statistical analysis concluded that combinations effectively improved plant traits by 65%–90% in the early growth stage and by 70%–90% in the maturity stage. The T6 treatment combination [i.e., biochar + R. leguminosarum + V. radiata (BC + RL + VR)] provided the most effective results in terms of growth, biomass, pod yield, and pigmentation content. In addition, this combination reduced the translocation of Cd in mustard plants by 70%–95%. The combination of BC + RL + VR effectively reduced Cd contamination of mustard tissue and provided a suitable growing environment for the plants. A post-harvesting soil analysis using X-ray diffraction (XRD) found that Cd was undetectable in soil. This provides clear confirmation that these approaches can lead to Cd soil remediation. Moreover, this study provided insight into the responses of different morphophysiological attributes of mustard plants to Cd stress and could aid in developing Cd stress tolerance in mustard plants.